PERANAN MAHASISWA KPPM DALAM MELAKSAKANAN KEGIATAN TAMBAHAN DI NAGORI PARIKSABUNGAN KECAMATAN DOLOK PARDAMEAN KABUPATEN SIMALUNGUN PROVINSI SUMATERA UTARA - Cristhyn Agustina Damanik; Ivanca Christine Rosaline Harahap; Gilbert Togi Silalahi; David Purba; Mardame Pangihutan Sinaga (Abdi Jurnal Publikasi, 2025)
The Practice Lecture and Student Service Activity (KPPM) aims to dedicate service to the community and help address various issues faced by society while applying the knowledge acquired through academic education. KPPM Period 4 was conducted from February 10 to March 7, 2025, in Pariksabungan Village, Dolok Pardamean District, Simalungun Regency. During this program, students were expected to assist residents in economic development, cultural preservation, and overall community welfare improvement. The implementation of KPPM Period 4 was based on field observations, interviews, and literature studies. Several activities carried out by students included improving facilities and cleanliness at the Pinus Hills tourist site, reducing waste in natural tourist attractions, cleaning water springs, installing village signboards, teaching and conducting extracurricular activities at SDN 091401 and SDN 095175, and participating in cleanliness activities at the Pariksabungan Village Office. The results of this study include: 1) Improving the facilities and cleanliness of the natural tourist attractions in Pariksabungan Village, 2) Enhancing and expanding students' interest in learning at SDN 091401 Pariksabungan and SDN 095175 Parbungaan, 3) Increasing public awareness of waste reduction in natural tourist attractions, 4) Strengthening collaboration between students and the Pariksabungan Village Government through cleanliness activities at the village office. This study recommends the need for improved coordination between KPPM students, the village government, and the local community in planning and implementing additional activities. Moreover, continuous evaluation of KPPM activities is necessary to ensure their sustainability and positive impact on the community.